Philantropinum in Kunvald - the regional school in the early 19th century = Philantropinum w Kunvald - szkoła regionalna w XIX wieku - Baar, Lubomír Vojtěch (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The owner of the Kunvald Château, the countess Maria Walburga, attempted to copy and improve the concept of Dessau Philanthropinum and inspired herself in the works of J. B. Basedow. She established her own Philantropinum in Kunvald village between 1792 and 1814. It is an interesting example of a school based on ideas from the late Enlightenment and Philanthropy, where children studied regardless of their gender, religion, or social status.
Keywords: regional education; Philanthropism; educational concept; social pedagogy; edukacja lokalna; filantropizm; koncept edukacyjny; pedagogika społeczna